White paper on antimicrobial stewardship in solid organ transplant recipients. Issue 1 (2nd August 2021) - So, Miranda; Hand, Jonathan; Forrest, Graeme; Pouch, Stephanie M.; Te, Helen; Ardura, Monica I.; Bartash, Rachel M.; Dadhania, Darshana M.; Edelman, Jeffrey; Ince, Dilek; Jorgenson, Margaret R.; Kabbani, Sarah; et al.
Abstract: Antimicrobial stewardship programs (ASPs) have made immense strides in optimizing antibiotic, antifungal, and antiviral use in clinical settings. However, although ASPs are required institutionally by regulatory agencies in the United States and Canada, they are not mandated for transplant centers or programs specifically. Despite the fact that solid organ transplant recipients in particular are at increased risk of infections from multidrug‐resistant organisms, due to host and donor factors and immunosuppressive therapy, there currently are little rigorous data regarding stewardship practices in solid organ transplant populations, and thus, no transplant‐specific requirements currently exist. Further complicating matters, transplant patients have a wide range of variability regarding their susceptibility to infection, as factors such as surgery of transplant, intensity of immunosuppression, and presence of drains or catheters in situ may modify the risk of infection. As such, it is not feasible to have a "one‐size‐fits‐all" style of stewardship for this patient population. The objective of this white paper is to identify opportunities, risk factors, and ASP strategies that should be assessed with solid organ transplant recipients to optimize antimicrobial use, while producing an overall improvement in patient outcomes. We hope it may serve as a springboard for development of future guidance and identification of research opportunities. Abstract : The authors identify opportunities and strategies that should be assessed with solid organ transplant recipients to optimize antimicrobial use while producing an overall improvement in patient outcomes.